Cross-validation of four different survey methods used to estimate illicit cigarette consumption in Brazil - André Salem Szklo; Roberto Iglesias; Michał Stokłosa; Valeska Carvalho Figueiredo; Kevin Welding; Paulo Roberto Borges de Souza Júnior; Alessandra Trindade Machado; Luís Felipe Leite Martins; Hannah Nascimento; Jeffrey Drope (2020)
Objective To cross-validate estimates of the size of the illicit cigarette trade based on the results of four different survey methods. Methods In 2018/2019, four non-industry-funded, large-scale studies were conducted in selected Brazilian cities: packs discarded in household garbage/PDG (1 city), packs littered in the streets/PLS (5 cities), a phone survey of tobacco users’ purchase behaviors/VIGITEL (5 cities), and a face-to-face household survey of tobacco users’ purchase behaviors/FTF-household (2 cities). The proportions of illicit cigarettes consumed were based on the price paid by smokers in their last purchase (VIGITEL or FTF-household) and/or direct observation of brand names and health warnings (PDG, PLS or FTF-household). Results Based on PLS, the share of packs that avoided taxation ranged from 30.4% (95% CI 25.6% to 35.7%) in Rio de Janeiro to 70.1% (95% CI 64.6% to 75.0%) in Campo Grande; and PDG conducted in Rio de Janeiro found an even lower proportion point estimate of illicit cigarette use (26.8%, 95% CI 25.1% to 28.6%). In FTF-household, the share of illicit cigarette consumption based on the self-reported price ranged from 29.1% (95% CI 22.4% to 35.7%) in Rio de Janeiro to 37.5% (95% CI 31.2% to 43.7%) in São Paulo, while estimates based on pack observation ranged from 29.9% (95% CI 23.3% to 36.5%) in Rio de Janeiro to 40.7% (95% CI 34.3% to 47.0%) in São Paulo. For all cities, VIGITEL presented the lowest levels of illicit consumption, and most illicit brands were produced in Paraguay. Conclusions Small differences in the estimated levels of illicit trade across methods were found, except for the phone survey. The cross-validation of estimates from independent studies is important to help effectively implement tobacco excise tax policy in Brazil and other low-income and middle-income countries.